Exploring psychosis and bipolar disorder in women: a critical review of the qualitative literature - Wittkowski, Anja (BMC Psychiatry, 2014)
BACKGROUND: The experiences of women with severe mental illness warrant particular consideration to identify the strategies they use to facilitate recovery. This review systematically examined women’s experiences of psychosis and bipolar disorder. METHODS: Following an extensive database search, 13 studies met inclusion criteria. Noblit and Hare’s metasynthesis approach was used to synthesise these qualitative studies exploring the experiences of 250 women, of which 78 (31.2%) were also mothers. RESULTS: Twelve sub-ordinate themes were identified and categorised into three overarching themes: 1) women’s beliefs about illness, 2) perceived consequences of illness, and 3) strategies used to cope with illness. Contextual factors and spiritual beliefs were found to be important in these women’s illness appraisals. Women incorporated diagnosis-related information into illness models if it was concordant with their existing beliefs. CONCLUSIONS: Women reported negative illness consequences relating to stigma, loss of self-determination and changes to relationships. They employed various strategies in order to cope with illness. Barriers to strategy use and clinical recommendations are presented.